Shrinkage simplex-centroid designs for a quadratic mixture model - Taha Hasan; Sajid Ali; Munir Ahmed (Journal of Industrial Engineering International, 2018)
A simplex-centroid design for q mixture components comprises of all possible subsets of the q components, present in equal proportions. The design does not contain full mixture blends except the overall centroid. In real-life situations, all mixture blends comprise of at least a minimum proportion of each component. Here, we introduce simplex-centroid designs which contain complete blends but with some loss in D-efficiency and stability in G-efficiency. We call such designs as shrinkage simplex-centroid designs. Furthermore, we use the proposed designs to generate component-amount designs by their projection.
Keywords: 650; Mixture experiment; Simplex-centroid design; D-optimality; G-optimality